Liberty and the infosphere: affiliation over citizenship - Bregman, Craig Howard (My University, 2018)
The title of my research report, Liberty and the Infosphere: Affiliation over Citizenship , speaks about an ideal of liberty, a maximal version, and then asks where such a version may be located, the proposition being that the infosphere, or more specifically, the internet offers such an environment. It then poses a supporting proposition in the form of the question: why we ought to a pursue a libertarian quest for freedom of affiliation online. This implies that we should affiliate with others, and that affiliation, as a collective-forming enterprise, is a better way of expressing liberty than that offered by the concept of citizenship. In pursuing this line of thought, I draw on a consequentialist frame of reference, arguing that liberty ought to guide us towards achieving the best results for both ourselves as well as others. This leads me further to propose a rule-consequentialist formulation of principles designed to maximise our experience of liberty by steering us through morally permissible actions and away from morally impermissible alternatives
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts, Applied Ethics for Professionals, Johannesburg, 2017
Keywords: Liberty; Liberalism